Hematological and Biochemical Changes in Dogs Naturally Infected With Dirofilaria repens - Wysmołek, Magdalena E.; Dobrzyński, Artur; Długosz, Ewa; Czopowicz, Michał; Wiśniewski, Marcin; Jurka, Piotr; Klockiewicz, Maciej (Frontiers in Veterinary Science, 2020)
Subcutaneous dirofilariosis is a zoonotic disease emerging throughout Europe caused by the filarial nematode Dirofilaria repens. Despite its increasing prevalence, there is a large gap in knowledge of the impact of the parasite on the host. Currently classified as being non-pathogenic, recent evidence suggests that skin dirofilariosis is associated with dermatological conditions including concomitant pruritus, neoplastic processes, inflammation and even blindness in dogs and humans. The aim of this study was to determine if natural canine D. repens infection leads to biological changes in the canine host. In a real-life veterinary clinic setting animals are often presented to clinicians for unrelated issues and D. repens is incidentally identified during inspection. As such, we compared hematological and biochemical parameters of 218 uninfected, and 197 dogs naturally infected with D. repens.Interestingly, animals infected with D. repens had lower numbers of lymphocytes (p<0.001), red blood cells (p<0.001), thrombocytes (p=0.025), decreased hematocrit (p<0.001), increased alkaline phosphatase (p=0.016) and creatinine activity (p=0.023) compared to uninfected dogs. We further selected a subpopulation of 214 dogs having prima facie hematological and biochemical results within normal reference ranges to evaluate the effect of D. repens infections in seemingly healthy dogs. Among these patients, 93 dogs infected with D. repens had lower numbers of lymphocytes (p=0.031), red blood cells (p=0.025), hematocrit (p=0.002), higher glucose levels (p=0.023) and border line elevated alkaline phosphatase levels (p=0.054) compared to 121 uninfected animals. Despite being categorized as asymptomatic, we have observed hematological and biochemical changes associated with D. repens infections in dogs, and our data suggest that dirofilariosis may induce a state of chronic stress. These results link the presence of skin dirofilariosis to biological changes in the canine host, suggesting a mechanism for pathogenicity and shedding new light on the host-parasite relationship.